(untitled) (Advances in Applied Mathematics and Mechanics, 2021)
Fluids engineering is extremely important in a wide variety of materials processing systems, such as soldering, welding, extrusion of plastics and other polymeric materials, Chemical Vapor Deposition (CVD), composite materials manufacturing. In particular, mixed convection due to moving surfaces is very important in these applications. Mixed convection in a channel, as a result of buoyancy and motion of one of its walls has received little research attention and few guidelines are available for choosing the best performing channel configuration, particularly when radiative effects are significant. In this study a numerical investigation of the effect of radiation on mixed convection in air due to the interaction between a buoyancy flow and an unheated moving plate induced flow in a uniformly heated convergent vertical channel is carried out. The moving plate has a constant velocity and moves in the buoyancy force direction. The principal walls of the channel are heated at uniform heat flux. The numerical analysis is accomplished by means of the commercial code Fluent. The effects of the wall emissivity, the minimum channel spacing, the converging angle and the moving plate velocity are investigated and results in terms of air velocity and temperature fields inside the channel and wall temperature profiles, both of the moving and the heated plates, are given. Nusselt numbers, both accounting and not for the radiative contribution to heat removal, are also presented.